2002
DOI: 10.1046/j.1460-9568.2002.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Speech processing activates visual cortex in congenitally blind humans

Abstract: Neurophysiological recordings and neuroimaging data in blind and deaf animals and humans suggest that perceptual functions may be organized differently after sensory deprivation. It has been argued that neural plasticity contributes to compensatory performance in blind humans, such as faster speech processing. The present study employed functional magnetic resonance imaging (fMRI) to map language-related brain activity in congenitally blind adults. Participants listened to sentences, with either an easy or a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
227
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(256 citation statements)
references
References 29 publications
23
227
1
5
Order By: Relevance
“…Based on the present findings, we conclude that the left-lateralized occipital activity during verbal tasks reflects language processing (25,35,41). However, prior studies have shown that regions of the occipital cortex in blind individuals also contribute to multiple nonverbal tasks, such as tactile discrimination and sound localization (42,43).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Based on the present findings, we conclude that the left-lateralized occipital activity during verbal tasks reflects language processing (25,35,41). However, prior studies have shown that regions of the occipital cortex in blind individuals also contribute to multiple nonverbal tasks, such as tactile discrimination and sound localization (42,43).…”
Section: Discussionsupporting
confidence: 67%
“…However, almost all prior studies of language in congenitally blind individuals have used single words. Suggestive evidence comes from one study that found an increase in occipital activity with increased grammatical complexity (35), but in that study the grammatically complex condition was also more difficult and led to greater activity in all examined brain regions and all groups. We therefore sought to establish whether the occipital areas of congenitally blind individuals are specifically sensitive to combinatorial linguistic processing.…”
mentioning
confidence: 98%
“…Resultados semelhantes foram descritos por outros autores (8,(11)(12)(13)(14)(15) . Na atenção direcionada para a audição periférica espacial, a localização de sons mostra-se significativamente melhor nos indivíduos cegos do que nos videntes, bem como nas tarefas de localização sonora monoaural (11) .…”
Section: Discussionunclassified
“…Imagens de ressonância magnética funcional de indiví-duos com privação sensorial demonstram que a plasticidade neuronal contribui para um melhor desempenho de indivíduos deficientes visuais, em atividades como processamento de fala (13) . A plasticidade neural é a "capacidade que o sistema nervoso central possui em modificar algumas das suas propriedades morfológicas e funcionais, em resposta às alterações do ambiente" (18) .…”
Section: Discussionunclassified
See 1 more Smart Citation